2021
DOI: 10.1111/php.13411
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Analysis of the Photobleaching of Protoporphyrin IX Used in Photodynamic Diagnosis and Therapy of Cancer

Abstract: Photobleaching and photoproduct formations are considered essential phenomena in improving the efficacy of photodynamic diagnosis and therapy (PDD and PDT). We investigated the photobleaching of protoporphyrin IX (PpIX) by measuring its concentration with mass spectrometry (MS). The reduction in the concentration of PpIX dissolved in dimethyl sulfoxide was measured during PDD and PDT conditions using lasers with wavelengths of 405 and 635 nm, respectively, at a power density of 10, 50 or 100 mW/cm2. The obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The spectroscopic analysis indicated that the rate at which PpIX photodegraded at the 633 nm peak did not vary with power density for either excitation wavelengths. This result is in line with our previous study of PpIX photobleaching under 405 and 635 nm irradiation 14 . The consistent photobleaching rate of ALA-induced PpIX over a range of power densities in tumor models and mouse skin in vivo has also been reported 31 , 32 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The spectroscopic analysis indicated that the rate at which PpIX photodegraded at the 633 nm peak did not vary with power density for either excitation wavelengths. This result is in line with our previous study of PpIX photobleaching under 405 and 635 nm irradiation 14 . The consistent photobleaching rate of ALA-induced PpIX over a range of power densities in tumor models and mouse skin in vivo has also been reported 31 , 32 .…”
Section: Discussionsupporting
confidence: 91%
“…This result is in line with our previous study of PpIX photobleaching under 405 and 635 nm irradiation. 14 The consistent photobleaching rate of ALA-induced PpIX over a range of power densities in tumor models and mouse skin in vivo has also been reported. 31,32 On the other hand, a discrepancy was seen in the findings reported by others, in which PpIX photobleaching was dependent on the power density.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…During photodynamic reactions, certain photosensitizers can also react with generated singlet oxygen ( 1 O 2 ), resulting in decreased photosensitizer concentration, absorbance, and fluorescence intensity. This phenomenon is termed photobleaching [56]. Due to the spectral characteristics of HPPH absorption, exposure to visible light after injection or fluorescence imaging prior to treatment may prompt the photosensitizer (PS) to reach an excited state prematurely, before its intended therapeutic activation.…”
Section: Combined Tumor Imaging and Treatmentmentioning
confidence: 99%